Pengaruh Metode Diskusi Presentasi Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas X SMA - Idos Idos; Sulaiman Sulaiman (Prodi Pendidikan Keagamaan Islam, 2022)
The study was conducted to determine the effect of the application of the discussion and presentation method on the learning outcomes of Islamic Religious Education and Budi Pekerti in class X students at SMA N 1 Kecamatan Gunuang Omeh. This research is a quantitative experiment with the type of One-Shot Case Study. A sample of 28 respondents was taken using the Saturated Sampling Technique. Data were taken using tests, questionnaires, and documentation. The discussion method of the X¹ variable, the X² presentation method, and the learning outcomes of the Y variable. The data were analyzed by prerequisite tests, namely, normality, homogeneity, linearity, multicollinearity, heteroscedasticity, and multiple linear regression tests, hypothesis testing with F test, T test, and R² test. Obtained F arithmetic 0.160<F table 4.20, and T arithmetic discussion method -0.339< T table 2.048, presentation method obtained T arithmetic -0.205<Ttable 2.048, simultaneous and partial conclusions discussion and presentation methods do not affect learning outcomes of Religious Education Islam and Morals of class X students at SMA N 1 Kecamatan Gunuang Omeh. The result of the R² test is 1.3%.